2015
DOI: 10.1016/j.dib.2015.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Glycan microarray analysis of the carbohydrate-recognition specificity of native and recombinant forms of the lectin ArtinM

Abstract: This article contains data related to the researc.h article entitled “Yeast-derived ArtinM shares structure, carbohydrate recognition, and biological effects with native ArtinM” by Cecílio et al. (2015) [1]. ArtinM, a D-mannose-binding lectin isolated from the seeds of Artocarpus heterophyllus, exerts immunomodulatory and regenerative activities through its Carbohydrate Recognition Domain (CRD) (Souza et al., 2013; Mariano et al., 2014 [2], [3]). The limited availability of the native lectin (n-ArtinM) led us … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 5 publications
0
9
0
2
Order By: Relevance
“…Although ArtinM recognizes primarily Manα1-3(Manα1-6)Man, which is the common core of N-glycans, the fine specificity of its binding is further determined by a secondary subsite of recognition. It interacts with other carbohydrate residues (Fuc and GlucNAc), which may be contained in the N-glycan, resulting in the particular binding property exhibited by this lectin 32 , 33 , 54 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although ArtinM recognizes primarily Manα1-3(Manα1-6)Man, which is the common core of N-glycans, the fine specificity of its binding is further determined by a secondary subsite of recognition. It interacts with other carbohydrate residues (Fuc and GlucNAc), which may be contained in the N-glycan, resulting in the particular binding property exhibited by this lectin 32 , 33 , 54 .…”
Section: Discussionmentioning
confidence: 99%
“…This activity was attributed to ArtinM interaction with TLR2 N-glycans 31 , which is followed by IL-12 production and establishment of Th1 immunity. The ArtinM effects were shown to depend on carbohydrate recognition because direct binding to TLR2 was inhibited by the trimannoside specifically targeted by ArtinM 32 , 33 , which constitutes the core of N-glycans. These data demonstrated that a carbohydrate recognition protein might function as a TLR agonist and exert immunomodulatory activity.…”
Section: Introductionmentioning
confidence: 99%
“…This research confirmed the preference of the ArtinM primary site for probes having the core structure Manα1–3[Manα1–6]Manβ1–4. It also showed the contribution of the secondary site of ArtinM to enhancing the affinity of the CRD for probes containing Fucα1–6 or GlcNAcα1–2 associated with Manα1–3[Manα1–6]Manβ1–4 [ 47 , 48 , 49 ]. The core structure Manα1–3[Manα1–6]Manβ1–4 recognized by ArtinM is also targeted by Morniga M [ 50 , 51 ], which is consistent with the marked correlation between the glycan-binding specificities and phylogenies of ArtinM and Morniga M [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The immunomodulatory properties of plant lectins have encouraged their screening for potential pharmaceutical applications, among them, the development of adjuvants. An important characteristic of certain plant lectins rely on their ability to interact with the mucosal epithelium and to be translocated across the gut, which may be exploited in vaccine formulations to induce mucosal and systemic immunity (47, 86) In the last few years, lectins from the jackfruit ( Artocarpus integrifolia ), ArtinM and Jacalin (JAC) have arisen as potential adjuvants in vaccines against protozoan parasites (80, 81, 116119). In particular, ArtinM, stimulates macrophages and dendritic cells to produce IL-12 (120), through ArtinM interaction with the N-glycans of TLR2 (121), inducing a biased Th1-immune response.…”
Section: Adjuvants: the Black Box Of Immunology Being Openedmentioning
confidence: 99%